Who will be a witness?: igniting activism for God's justice, love, and deliverance - Hart, Drew G. I. (Herald Press, 2020)
"Who Will Be a Witness offers a vision for communities of faith to organize for deliverance and justice in their neighborhoods, states, and nation as an essential part of living out the call of Jesus. Author Drew G. I. Hart provides incisive insights into Scripture and history, along with illuminating personal stories, to help us identify how the witness of the church has become mangled by Christendom, white supremacy, and religious nationalism. Hart provides a wide range of options for congregations seeking to give witness to Jesus' ethic of love for and solidarity with the vulnerable. At a time when many feel disillusioned and distressed, Hart calls the church to action, offering a way forward that is deeply rooted in the life and witness of Jesus. Dr. Hart's testimony is powerful, personal, and profound, serving as a compass that points the church to the future and offers us a path toward meaningful social change and a more faithful witness to the way of Jesus"--